Comparison of novice versus expert for a hang clean lift: Muscle activation and temporal differences - Bauer, J.; Fry, A.; Carter, C. (Medicine & Science in Sports & Exercise, 1997)
Differences in muscle activation patterns between phases of a skilled movement were analyzed in novice and expert weightlifters. Only one S in each category was assessed. Repetition completion times, lumbar maximum EMG, and lumbar and thoracic time to peak EMG were all better in the expert performer. These results suggest the following: as greater skill is acquired, ballistic repetition becomes even more explosive, experts are able to recruit motor units faster than novices, and EMG may be a suitable means of measuring skill acquisition. Implication: The characteristics of high-level performance in skill execution indicate some of the training parameters that should be emphasized if the skill involves explosive power. Training items should emphasize speed of execution, a conscious attempt to expend as much energy as possible in each task trial, and produce effort over the total range of muscles activated in the movement, not just a few prime movers.